2017
DOI: 10.1159/000452163
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Aflibercept as Rescue Therapy for Post-Radiation Cystoid Macular Edema Resistant to Intravitreal Bevacizumab: Outcomes at 1 Year

Abstract: Background/Aims: To investigate the efficacy of intravitreal aflibercept as rescue therapy for post-radiation cystoid macular edema (CME) resistant to prior treatment with intravitreal bevacizumab (IVB). Methods: Retrospective, interventional, case-controlled series. Eyes with persistent post-radiation CME were treated with intravitreal aflibercept (2 mg/0.05 mL). Central macular thickness (CMT) and visual acuity were compared to a matched control group treated with only IVB at 1 year. Results: Ten eyes of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Aflibercept (Eylea; Regeneron Pharmaceuticals, Inc, Tarrytown, NY, USA) is another anti-VEGF agent, which has revealed promising effect in cases of bevacizumab-resistant postradiation cystoid macular edema (CME). [ 5 ] Thus, here, we present a case of primary uveal melanoma with bevacizumab-resistant CME and demonstrate the role of aflibercept as a potential therapy.…”
Section: Introductionmentioning
confidence: 82%
“…Aflibercept (Eylea; Regeneron Pharmaceuticals, Inc, Tarrytown, NY, USA) is another anti-VEGF agent, which has revealed promising effect in cases of bevacizumab-resistant postradiation cystoid macular edema (CME). [ 5 ] Thus, here, we present a case of primary uveal melanoma with bevacizumab-resistant CME and demonstrate the role of aflibercept as a potential therapy.…”
Section: Introductionmentioning
confidence: 82%
“…With newer understanding of the early presentation of radiation retinopathy and the impact it may have on anatomic and visual outcome, many investigators have more recently begun earlier treatments including laser photocoagulation, intravitreal steroids, and/or intravitreal anti-VEGFs. 4,5,23,[28][29][30][31][32][33] Advanced imaging of postradiation-treated eyes has advanced our understanding of radiation maculopathy. The ability to detect early, clinically significant macular edema was enhanced with SD-OCT and swept-source OCT.…”
Section: Discussionmentioning
confidence: 99%
“…In our center, best-care practices for patients unresponsive to short-course bevacizumab were to transition to treatment with intravitreal triamcinolone acetonide in a combined approach. 31 Multiple investigators have noted marked improvement in retinal anatomy but reported variable improvements in VA. 32,33 Virtually all of these reports were retrospective and nonstandardized, but the increasing recognition of improved outcomes has slowly led to the incorporation of intravitreal injection therapy from a small handful of ocular oncology centers to virtually all centers in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Intravitreal injection therapy has shown to keep visual acuity and macular anatomy stable in several studies. [5][6][7] Additionally, appropriate treatment modality regarding injection intervals prior to the hurricane may have aided in improving outcomes despite the delay in therapy.…”
Section: Discussionmentioning
confidence: 99%